Perancangan Branding Visual untuk Meningkatkan Brand Awareness Gerbang Taru Bali: Pengabdian - I Gusti Ayu Agung Aristi Putri; Arief Yulianto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The growth of the creative economy in Indonesia positions visual communication design as a strategic element in strengthening the image and identity of various entities, including Micro, Small, and Medium Enterprises (MSMEs). Gerbang Taru Bali, an MSME engaged in agriculture and based in Denpasar, Bali, faces challenges in building brand awareness due to the absence of a structured visual branding system. This community service project aims to design the visual identity of Gerbang Taru Bali through a participatory design approach that actively involves the partner. The methods used include observation, reference study, concept development, testing, education, and evaluation. The outcomes of this activity include the development of visual identity elements and usage guidelines that are designed consistently and contextually. Through the application of this visual branding, Gerbang Taru Bali is expected to enhance its visual appeal, strengthen public perception, and establish a professional and competitive image. Furthermore, this initiative contributes to providing visual solutions, improving visual literacy, and increasing the partner’s capacity to manage branding independently and sustainably.